1 - Liberal models of Capitalist Development in Africa: Ivory Coast - Nyongo , P. Anyang (Africa Development, 1978)
In this paper, the author attempts to describe and analyze the development model currently in force in Côte d'Ivoire. This is the model of development through dependent peripheral capitalism. After situating its birth and its development in the historical colonial perspective and describing its evolution in the post-colonial era, the author quickly paints a picture of the main structures and economic activities of Côte d'Ivoire. These consist of cash-crop agriculture (mainly coffee) assumed by the peasants, whose products are purchased by the large French multinational companies through the intermediary of Lebanese-Syrian traders. On this basic structure, inherited from colonization, the post-colonial state, together with international private capital, is trying to build a more diversified economy by investing in new sectors. In so doing, it consolidates the hegemony of international capital over the nascent national agrarian and commercial bourgeoisie, of which it is precisely the political and legal instrument and from which it receives its legitimacy and stability. Objectively opposed to this national bourgeoisie are the producers, the workers and the rural unemployed; urban workers and unemployed. It also analyzes the dynamics of fractions, groups and social classes with regard to the degree of their integration into the system, the role they play in it and their access to the infrastructures and resources available for their development. He concludes by noting that the capitalist path of development can work well in Africa, despite current structures of dependency. It is important, he thinks, to detect the promising elements in the initiatives taken by the various fractions of the African bourgeoisies.